The Effectiveness of SPSS-Assisted Troubleshooting Tutorial Videos in Virtual Classroom Against Student Statistics Performance - Arbain Arbain (JME (Journal of Mathematics Education), 2021)
One of the learning challenges during the Covid-19 pandemic is the low mastery of material by students, especially abstract material such as statistics. As an alternative solution, statistical learning is carried out using problem solving video tutorials assisted by SPSS to further measure its effectiveness on academic performance. This type of research is true-experimental with Posttest Only Control Design. The sample of this study was students of the management study program of the Faculty of Social and Political Sciences, Ninebelas November Kolaka University who took statistics courses in the odd semester of the 2020 Academic Year which consisted of two classes, namely class C with 32 students and class D with 33 students. The instrument used is a learning achievement test in the form of an essay. The research data were analyzed using one sample t-test and independent sample t-test. The results of data analysis showed that the statistical performance of students taught using SPSS-assisted videos was better than those taught using learning modules.